Les Europeras de John Cage : de l’opéra au cirque - Antonia Rigaud (Sillages Critiques)
This article addresses John Cage’s ambiguous relationship with theatre throughout his career. Influenced early by Artaud and Stein, he often referred to theatre and understood his own art project as a reflection on theatricality and performance. The Europeras, written late in his career, testify to his attempt to associate his artistic experimentation with theater while pushing on the limits of theatre. The prominent position Cage gave to the theatre in contrast to the rarity of his theatrical work pieces is emblematic of his ambition to re-think the theatre as a locus of experimentation.